(untitled) (Bangladesh Journal of Zoology, 2010)
A total of 49 birds (10 hatchlings, 20 fledglings and 19 adult) of the Little Cormorant (Phalacrocorax niger) was taken for the study of morphometric analysis. The study was conducted at Dhaka Zoo, Mirpur and in a village under Chandpur district from January 2003 to December 2004. The average body weights of hatchlings, male fledglings, female fledglings, adult males and adult females were 10.45 ± 3.6 g, 573.5 ± 49.04 g, 520 ± 46.37 g, 527 ± 43.79 g and 460 ± 10.31 g, respectively. The body length of these birds were 7.55 ± 1.24 cm, 53.32 ± 2.25 cm, 51.24 ± 1.25 cm, 52.37 ± 3.5 cm and 51.42 ± 1.25 cm, respectively. The wing lengths of these birds were 3.36 ± 0.635 cm, 37.62 ± 0.613 cm, 36.6 ± 0.37 cm, 37.86 ± 2.03 cm and 36.88 ± 1.23 cm, respectively. The tail lengths of the male fledglings, female fledglings, adult males and adult females were 14.4 ± 0.524 cm, 11.98 ± 0.716 cm, 16.98 ± 0.498cm, 13.5 ± 0.612 cm, respectively. The leg length of the hatchlings, male fledglings, female fledglings, adult males and adult females were 3.36 ± 0.58, 12.76 ± 0.83, 18.53 ± 0.64, 18.41 ± 1.55, 10 ± 0.64 cm, respectively. Bangladesh J. Zool. 38(1): 113-118, 2010